2021
DOI: 10.1016/j.ctro.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Determining the safety of ultrafocal salvage high-dose-rate brachytherapy for radiorecurrent prostate cancer: A toxicity assessment of 150 patients

Abstract: Highlights Severe toxicity is as low as 3% (GU), 0% (GI) and 15% (ED). Lower impact is predicted for patients with favorable function at baseline. Lower dose to the urethra (D10% <17 Gy) may prevent urinary symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The readily available nature and reasonable side effect profile to these medication classes suggest that sHDR-BT acute complications may be easily managed. Our study also shows comparable acute GI results to studies in the literature, as seen in Table 7 [14][15][16][34][35][36][37][38][39][40][41][42][43][44][45][46]. Ménard et al [11] used MRI-only or MRI-TRUS guidance sHDR-BT, and reported similar toxicity outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…The readily available nature and reasonable side effect profile to these medication classes suggest that sHDR-BT acute complications may be easily managed. Our study also shows comparable acute GI results to studies in the literature, as seen in Table 7 [14][15][16][34][35][36][37][38][39][40][41][42][43][44][45][46]. Ménard et al [11] used MRI-only or MRI-TRUS guidance sHDR-BT, and reported similar toxicity outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…However the timing of initiation, type of androgen blockade and its role in asymptomatic stages remains poorly defined. ADT has a temporary suppressive effect on the disease, halting its progression for a mean of 2-3 years before the tumor becomes hormone-resistant (66). It is therefore a palliative treatment with no potential of cure.…”
Section: Low-riskmentioning
confidence: 99%
“…Furthermore, delayed tumor regression may cause false positives. Biopsies should therefore not be taken before 24 months of follow-up [66]. Even after two years, routine post-radiotherapy biopsies are of limited added value to regular PSA-testing, and should only be considered in case of biochemical failure [67].…”
Section: Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation